2001
DOI: 10.1080/10587250108035575
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Bulk-Mediated Photoalignment of Doped Liquid Crystal

Abstract: We have found that producing a light-induced easy axis in a liquid crystal cell doped with methyl red can result in surface director reorientation both toward and outward the polarization of the incident light. This pointed out two different mechanisms of light-induced anchoring in the system. We proposed that these mechanisms are light-induced anisotropy in the adsorbed MR-layer and light-induced adsorption of MR molecules on the substrate. The study of light-induced anchoring in the isotropic phase showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Both papers showed that irradiation in the isotropic phase results in an anisotropic distribution of the adsorbed dye molecules in the LC phase, the effect being hidden when the material is in the isotropic phase. The induced easy axis could be either parallel and perpendicular to the polarization of the incident light, depending on light intensity [14] or, more precisely, on the light dose [15]. This behaviour was explained by two mechanisms: light-induced adsorption of MR molecules on the irradiated surface (already discussed) and (this is the novelty)…”
Section: The Dark Adsorbed Layermentioning
confidence: 96%
See 2 more Smart Citations
“…Both papers showed that irradiation in the isotropic phase results in an anisotropic distribution of the adsorbed dye molecules in the LC phase, the effect being hidden when the material is in the isotropic phase. The induced easy axis could be either parallel and perpendicular to the polarization of the incident light, depending on light intensity [14] or, more precisely, on the light dose [15]. This behaviour was explained by two mechanisms: light-induced adsorption of MR molecules on the irradiated surface (already discussed) and (this is the novelty)…”
Section: The Dark Adsorbed Layermentioning
confidence: 96%
“…Several papers dated 2001 predicted the formation of a layer of MR molecules adsorbed on the cell inner substrates before cell irradiation [14][15][16][17]. Papers [14] and [15] describe the director reorientation due to cell irradiation in the isotropic phase.…”
Section: The Dark Adsorbed Layermentioning
confidence: 98%
See 1 more Smart Citation
“…In present LCD production a lot of techniques for creation of the planar or tilted homogeneous alignment of liquid crystal molecules (e.g., vacuum thermal deposition or electron beam evaporation of oxides, rubbing of the polymer films, photoalignment, plasma treatment and others [1][2][3][4][5][6]) are used. But these technologies have many imperfections.…”
Section: Introductionmentioning
confidence: 99%